Association of oral estradiol dose/levels with coagulation measures in early/late postmenopausal women - I. Sriprasert (2020)
© 2020, © 2020 International Menopause Society. Objective: This study evaluated associations of estradiol (E2) dose and serum E2 levels with coagulation/anti-coagulation measures in early (<6 years) compared with late (≥10 years) postmenopausal women. Methods: Postmenopausal women from the REPLENISH trial tested four formulations of oral combined E2 and progesterone compared with placebo. Mixed-effects linear models tested the association of E2 dose and serum E2 levels with the prothrombin time (PT), the activated partial thromboplastin time (APTT), antithrombin (ATHRM), fibrinogen (FIBRINO), protein C (PROTC), and protein S (PROTS), assessed five times over 12 months. Results: Among 1215 early and 297 late postmenopausal women, the E2 dose was statistically significantly inversely associated with the APTT in early postmenopause, PROTC in late postmenopause, and with the PT, ATHRM, and PROTS in both groups. Serum E2 levels were statistically significantly inversely associated with the APTT, PROTS, and FIBRINO in early postmenopause, the PT in late postmenopause, and ATHRM and PROTC in both groups. With longer time since menopause, the inverse E2 dose effect and serum E2 effects became stronger. Conclusion: Increasing E2 dose and serum E2 levels were associated with changes in coagulation/anti-coagulation measures. The associations were stronger among women ≥10 years since menopause when initiating E2. The timing of E2 therapy, E2 dose, and serum E2 levels relative to time since menopause may modify the venous thromboembolism risk.